Ocorrência de anormalidades morfológicas externas em caranguejos marinhos (Decapoda, Brachyura) no litoral norte do estado de são paulo - Fransozo, Adilson [UNESP]; Teixeira, Gustavo Monteiro; Gomes, Rafael Rocco [UNESP]; Silva, José Carlos; Bolla Jr., Eduardo Antonio [UNESP] (Universidade Estadual de Maringa, 2012)
Deformities and abnormalities in crustaceans have been associated to genetic problem, which occurred during molt process, damage caused by ectobionts, predators or environmental stress caused by chemical wastes. Some crab specimens collected in the São Paulo littoral were found having body abnormalities. They belong to the following crab species: Callinectes ornatus (Ordway, 1863), Arenaeus cribrarius (Lamarck, 1818) and Leurocyclus tuberculosus (H. Milne Edwards; Lucas, 1843). Samplings were performed by trawling during July 2008, August and October 2009 at the Ubatuba region, São Paulo State, Brazil. Body abnormalities were verified in the cheliped dactyl (C. ornatus an adult male), carapace deformities (A. cribrarius an adult male) and abdominal alterations (C. ornatus an adult female; L. tuberculosus an adult male and an ovigerous female). The record and analysis of such occurrences can help in the distinction of natural or human impact caused alterations. In this way, the occurrence study of this kind of body alterations could provide tools in order to control unprotected environmental areas, as well as bring subsides to understand the unusual variations during the ontogeny of important species in the benthic community.
Occurrence of external morphological abnormalities in marine crabs (Decapoda, Brachyura) from North Coast of the São Paulo State
Keywords: Arenaeus cribrarius; Callinectes ornatus; Chelipeds and carapace; Crabs abnormalities; Leurocyclus tuberculosus; abdominal malformation; benthic fauna; Brazil; carapase deformity; congenital malformation; crab; environmental protection; female; limb malformation; male; marine species; morphological trait; nonhuman; Brachyura; Crustacea; Decapoda (Crustacea)